2017
DOI: 10.4103/2249-4863.214981
|View full text |Cite
|
Sign up to set email alerts
|

A case–control study on environmental and biological risk factors for renal calculi persisting in a coastal Union Territory, India

Abstract: Background and Objectives:Renal stone disease is a common disorder of the urinary tract and also a significant problem because of incidence, recurrence, and severe consequences. The complex pathogenetic mechanisms of renal stone formation involve both biologic and environmental risk factors. The present study was performed to identify the role of these parameters among renal stone patients and normal individuals from a coastal union territory region in South India.Methods:The authors conducted a case–control s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…Similarly, the retrospective investigation by Tang K, et al reported prevalence of kidney stones in adult patients (52 years), which may be due to more clinical trials that have been designed exclusively for adult patients [5]. Other risk factors that attributed to the development of stones in adult patients were changes in eating habits, lifestyle, alcohol consumption, sedentary lifestyle, and obesity [10].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the retrospective investigation by Tang K, et al reported prevalence of kidney stones in adult patients (52 years), which may be due to more clinical trials that have been designed exclusively for adult patients [5]. Other risk factors that attributed to the development of stones in adult patients were changes in eating habits, lifestyle, alcohol consumption, sedentary lifestyle, and obesity [10].…”
Section: Discussionmentioning
confidence: 99%
“…Socio-demographic elements such as age, gender, educational status, and socioeconomic class play a role in the formation of kidney stones. Furthermore, other risk factors that contribute to the development of renal stones include inadequate water intake, water intake without filtration, a high intake of raw vegetables, daily tea intake, inactive lifestyle, history of renal stone in the family, smoking, high serum level of lipids, diabetes mellitus, and hypertension [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Urinary stones are major painful health problems that can lead to impaired urinary functions, renal loss and bladder cancer. 1 Their prevalence varies between 2% and 15%. [2][3][4] In Turkey, a study has revealed an overall prevalence of urinary stones of 11.1% 3 and it was decided that they were endemic problems in Turkey.…”
Section: Introductionmentioning
confidence: 99%
“…The risk factors of urinary stones include ageing, male gender, diabetes mellitus, urinary infection, family history, inadequate fluid intake and excessive consumption of oxalate, calcium and vitamin D. 1,6 The causes of kidney stones also vary according to the type of stones. 7 There are five types of urinary stones including calcium and/or oxalate stones, cystine stones, xanthine stones, uric acid stones, struvite/infection stones.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation